Serum hyaluronic acid concentration predicts the progression of joint space narrowing in normal knees and established knee osteoarthritis – a five-year prospective cohort study. Issue 1 (December 2015) - Sasaki, Eiji; Tsuda, Eiichi; Yamamoto, Yuji; Maeda, Shugo; Inoue, Ryo; Chiba, Daisuke; Fujita, Hiroshi; Takahashi, Ippei; Umeda, Takashi; Nakaji, Shigeyuki; Ishibashi, Yasuyuki
Abstract Introduction Serum hyaluronic acid (sHA) is a serum biomarker for knee osteoarthritis (OA). Although sHA concentration is elevated in patients with knee OA, the relationship between serum concentration and disease progression remains unclear. We examined the relationship between sHA concentration and radiographic progression of knee OA in a cohort of individuals followed for 5 years. Methods We prospectively enrolled 444 individuals and measured their sHA concentrations at baseline. Anterior-posterior weight bearing knee radiographs were obtained at baseline and the 5-year endpoint. Osteoarthritic knee changes were classified according to Kellgren–Lawrence (KL) grade, and joint space narrowing (JSN) was measured using a Knee Osteoarthritis Computer-Aided Diagnosis (KOACAD) system. Correlations between sHA concentration, progression in KL grade, and JSN were assessed using regression models, taking into account potentially confounding factors. Results OA progressed from KL grades 0 or 1 in 129 of the 323 knees, and from KL grades 2 or 3 in 61 of the 119 knees. Higher sHA concentrations were correlated with KL grade progression (p = 0.004). The mean JSN, as assessed by KOACAD over 5 years, was 0.23 ± 0.55 mm, and sHA concentration was positively correlated with progression of JSN in KL grades 0 or 1 (p = 0.021) and KL grades 2 or 3 (p = 0.008) knees. Conclusion Serum HA concentration was positively correlated with progression of KL grade. sHA was also positively correlated with progression of JSN in knees with and without OA, suggesting that sHA concentration may be a useful predictor of knee OA progression.